Bioremediation Of Soil Of The Kola Peninsula (Murmansk Region) Contaminated With Diesel Fuel - Maria V. Korneykova; Vladimir A. Myazin; Nadezhda V. Fokina; Alexandra A. Chaporgina (GEOGRAPHY, ENVIRONMENT, SUSTAINABILITY, 2021)
This work focuses on the creation and use of associations of hydrocarbon-oxidizing microorganisms. Bioremediation of soils with the help of mixed cultural and associations of microorganisms provides wider adaptive possibilities than individual species. This is especially important in conditions of short northern summer. The results of field experiments showed that microbial associations based on indigenous microorganisms (bacteria Pseudomonas fluorescens, P. putida, P. baetica, Microbacterium paraoxydans and fungi Penicillium commune, P. canescens st. 1, P. simplicissimum st. 1) with mineral fertilizers reduced the content of total petroleum hydrocarbons in the Hortic Arthrosol soil of the Kola Peninsula by 82% over 120 days. Also, the microbial associations with mineral fertilizers had a positive effect on the physical properties of the soil, increasing its humidity. The bacterial-fungi associations changed the number, abundance and structure of the indigenous community of microorganisms. Penicillium canescens, which was included in the composition of fungi association, became dominant. During the rapid decomposition of hydrocarbons are released to the soil toxic intermediates or metabolites of the microbial oxidation of hydrocarbons. Hydrocarbon oxidizing microfungi suppressed the germination of test plant seeds to one degree or another. Penicillium commune fungal metabolites inhibited seed germination only by 29% for Lepidium sativum L. and 24% for Triticum aestivum L. This species can be used for bioremediation of petroleum contaminated soils.